Degradable coated paper and preparation method thereof
By using degradable chitosan and modified talc in coating paper, the problems of single and non-degradable functions of existing coating paper are solved, and multiple functions of degradable, thermal insulation and antibacteriality are realized, and production is reduced Cost, suitable for large-scale industrial applications.
Patent Information
- Application Number
- CN202411614400.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-30
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing coating paper has a single function and is non-degradable, resulting in environmental pollution problems.
Degradable chitosan and modified talc powder are used to develop a degradable membrane paper. By modifying talc powder, the insulation performance and cost-reducing efficiency of membrane paper are improved, ensuring the biodegradability and environmental significance of the material. .
It realizes the multiple functions of coating paper, including degradability, thermal insulation and antibacterial, reduces production costs, and has high environmental protection of the materials, making it suitable for large-scale industrial applications.
Smart Images

Figure CN119465699A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and more specifically, relates to a degradable coated paper and a preparation method thereof. Background Art
[0002] At present, coated paper is widely used in packaging fields such as daily necessities, electronics, food, chemicals, and medicine. Antibacterial coated paper with thermal insulation performance will further enrich the functions and uses of coated paper. However, coated paper in these application fields is basically a disposable product, which not only consumes a lot of paper, but also causes environmental problems after being discarded. Therefore, it is of practical significance to develop a degradable and environmentally friendly coated paper.
[0003] As plastic pollution becomes increasingly serious, domestic and foreign plastic pollution prevention policies become more stringent, and relevant policies continue to advance. It is expected that the demand for replacement of disposable and non-degradable plastic products will be gradually released. From the perspective of the downstream application market, the market segments covered by alternative plastics involve disposable plastic bags, express packaging, disposable tableware, and other segments. Polylactic acid (PLA) is considered to be the main alternative product to solve the "white pollution" of plastic products. It is also the most industrialized biodegradable material at present. The development of the PLA industry will enter the next golden period. Data shows that by 2025, the market space for degradable plastics related to the domestic plastic restriction order is expected to reach 4.11 million tons. This huge incremental market will lay the foundation for the development of the PLA industry. Antibacterial coated paper with thermal insulation function will further expand the use scenarios of coated paper, such as coffee, milk tea, food insulation and cold preservation, fresh food preservation, etc. As people pay more and more attention to food safety and extend shelf life, the development of antibacterial packaging materials has also been promoted. Due to some defects of polylactic acid itself, such as high brittleness and easy degradation, there are still limitations in the actual production and application of polylactic acid in lamination. Therefore, it is necessary to modify polylactic acid to develop more practical value.
[0004] Corresponding improvements have also been made to the above problems, such as China Patent Application No. CN202211514998.8, published on April 9, 2024. The patent discloses a biodegradable PLA coating material and a coating product based thereon, which is a grafted coated cellulose nanocrystal added as a modifier to a polylactic acid resin (PLA). The biodegradable PLA coating material formula provided by the present invention utilizes two-dimensional modified cellulose nanocrystals to be oriented in PLA molecules, and reinforces and toughens PLA in a high orientation form, and the acetylated cellulose nanocrystals can effectively improve the agglomeration and phase separation problems of nanocrystalline powder in PLA resin, effectively avoid the problem of degradation rate loss after toughening PLA by other elastomers, permanently improve the mechanical strength and impact strength of PLA blends, give PLA the same biodegradability and light transmittance, and improve the high added value and performance of biodegradable PLA products. The disadvantage of this patent is that the preparation cost of grafted coated cellulose nanocrystals is relatively high, especially when it needs to undergo complex surface modification treatment, which may limit its competitiveness in large-scale industrial applications.
[0005] Another example is Chinese patent application number CN202110047889.9, published on May 14, 2021. The patent discloses a biodegradable low-temperature resistant coated paper, including a base paper and a coating layer. The coating layer material includes 70-85wt% polycaprolactone composition, 5-10wt% polylactic acid, 5-10wt% biodegradable thermoplastic polyurethane, 2-5wt% modification aid, 0.1-1wt% antioxidant, and 1-10wt% antibacterial agent. The preparation method of the coated paper includes the following steps: blending polycaprolactone and the modification aid, melting, extruding, cooling granulation and drying; then blending the obtained material with other components, melting, extruding, cooling granulation, drying and dehumidifying to obtain the coating layer material; finally, the coating layer material is subjected to coating and drying treatment on the base paper through a coating machine to obtain the coated paper. The shortcoming of this patent is that polycaprolactone is not completely biodegradable, and the degradation rate may be limited under certain environmental conditions. Summary of the invention
[0006] 1. Problems to be solved
[0007] In view of the problem that the existing coated paper has a single function, the present invention provides a degradable coated paper and a preparation method thereof. The present invention achieves the antibacterial purpose by selecting degradable chitosan, while not affecting the mechanical properties of the coated paper; the purpose of heat preservation and cost reduction and efficiency improvement is achieved by modifying talcum powder, so that the finally prepared degradable coated paper has multiple functions of degradability, heat preservation and antibacterial; at the same time, the raw materials used are all biodegradable, which has high environmental significance. The entire preparation method is simple to operate, has high convenience and efficiency, so that the preparation method can be put into large-scale production and has a high prospect for use.
[0008] 2. Technical solution
[0009] To solve the above problems, the present invention adopts the following technical solutions.
[0010] A degradable coated paper comprises a base paper and a coating layer, wherein the coating layer comprises the following components by weight: 50 to 80 parts of polylactic acid, 10 to 25 parts of poly(hexane succinate terephthalate); 1 to 5 parts of biodegradable chitosan, 10 to 20 parts of modified talcum powder, 0.3 to 1.0 parts of a plasticizer, 0.2 to 1.0 parts of a lubricant, 0.2 to 0.5 parts of an antioxidant, and 0.2 to 0.5 parts of a compatibilizer; the modified talcum powder is talcum powder with a silane coupling agent coated on its surface.
[0011] By adopting the above technical scheme, the compatibility between polylactic acid, poly(hexylene succinate terephthalate) and modified talcum powder is enhanced through the action of the compatibilizer, and the mechanical strength of the coated paper can be further increased on the basis of maintaining the original good degradability and mechanical properties of polylactic acid, and the biodegradable chitosan has good antibacterial properties, and can achieve better antibacterial effects when combined with polylactic acid; at the same time, it helps to improve the processing performance and mechanical properties of the material, making the coated paper easier to operate and form in the subsequent production process; and the brittleness of polylactic acid is improved by poly(hexylene succinate terephthalate), thereby improving the flexibility and ductility of the entire raw material; the addition of modified talcum powder can significantly improve the overall mechanical properties of the coated paper, and give the coated paper thermal insulation properties, and as a natural mineral, it has low cost, which plays a role in reducing costs and increasing efficiency; the core raw materials of the entire degradable coated paper are all degradable materials or renewable materials, which help to reduce environmental pollution and promote sustainable development; the prepared coated material can withstand a gram weight of 0.6N / 30mm, which meets the requirements of general coated paper cups.
[0012] Furthermore, the modified talcum powder is food grade talcum powder, the size of the modified talcum powder is 2500-3000 mesh, and the residual total water content is 0.02-0.1wt%.
[0013] By adopting the above technical scheme, the size of the modified talcum powder is limited to 2500-3000 mesh. Talc powder within this size range belongs to fine talcum powder. The fine talcum powder has a flaky structure and can be evenly dispersed in the resin in a layered manner, just like a diamond structure mesh embedded in a cement structure. In addition to maintaining the advantages of the plastic itself, it can form a reinforced support form with good mechanical properties, further enhance the physical properties of plastic products, and also have obvious thermal insulation effects; and food-grade talcum powder meets food safety standards, so adding it to degradable coated paper will not cause harm to human health, thereby ensuring the safety of the coated paper.
[0014] Furthermore, the plasticizer is acetyl tributyl citrate ATBC, the antioxidant is at least one of 1010 or 168, and the compatibilizer is Xibond 2025 from Polyscop.
[0015] A method for preparing the degradable coated paper as described in any one of the above, comprising the following steps:
[0016] S1: drying polylactic acid, poly(hexane succinate terephthalate) and biodegradable chitosan;
[0017] S2: mixing a plasticizer, a compatibilizer, a lubricant, an antioxidant, and the dried polylactic acid, poly(hexane succinate terephthalate), and biodegradable chitosan to obtain a premix;
[0018] S3: adding modified talcum powder to the premix to obtain a mixed modified material;
[0019] S4: putting the mixed modified material into a twin-screw extruder for extrusion granulation to obtain a coating layer material;
[0020] S5: coating the base paper with a coating layer material to obtain a degradable coated paper.
[0021] By adopting the above technical scheme, polylactic acid, poly(hexanediol succinate terephthalate) and biodegradable chitosan are first dried. Since they are materials with relatively strong hygroscopicity, they are easy to absorb moisture in the air during the mixing process if not dried, resulting in uneven mixing or affecting the performance of the coating layer material; then, different raw materials are added in batches, which is conducive to controlling the reaction process, better controlling the production rhythm, avoiding uneven mixing or equipment overload caused by adding too many raw materials at one time, ensuring that each step achieves the expected effect, and helping to reduce the unevenness in the mixing process, thereby improving quality, improving production efficiency, and reducing waste and loss in the production process.
[0022] Furthermore, in step S1, the drying time of polylactic acid, poly(hexane succinate terephthalate) and biodegradable chitosan is 7 to 9 hours, and the drying temperature is 45 to 55°C.
[0023] By adopting the above technical scheme, the drying time and drying temperature of polylactic acid, poly(hexanediol succinate terephthalate) and biodegradable chitosan are strictly controlled. Because polylactic acid and biodegradable chitosan are heat-sensitive materials, too high temperature will cause their molecular chains to break and thermal degradation to occur, thereby affecting the performance and quality of the coating layer material; too low temperature will lead to slow drying progress, incomplete drying and increased production costs and energy consumption; too long drying time will increase production costs and energy consumption; if the drying time is too short, it may not be possible to completely remove the moisture in the raw materials.
[0024] Furthermore, when the mixed modified material is fed into the twin-screw extruder for extrusion granulation in step S4, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone, and the temperature of the heating zone is set to rise from 120°C to 200°C; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is 170°C to 180°C.
[0025] By adopting the above technical scheme, when extrusion granulation is performed, the temperature is first gradually increased to avoid excessive thermal stress of the material caused by rapid temperature increase, thereby destroying the stability of the material; and the temperature is increased to 200°C and kept warm to ensure that the mixed modified material is completely plasticized, so that it has good fluidity and plasticity, providing favorable conditions for subsequent extrusion granulation; finally, the mixed modified material is gradually cooled to avoid overheating, resulting in decomposition or degradation and destroying its stability; the setting of the temperature gradient not only helps the gradual melting and mixing of the mixed modified material, but also optimizes the energy consumption and efficiency during the extrusion granulation process.
[0026] Furthermore, when the base paper is coated in step S5, the base paper thickness is 1 mm, and the coating amount of the coating material is 30 g / m 2 By adopting the above technical solution, the precise control of the coating amount can achieve its uniform distribution on the base paper without causing waste of resources and increase of costs.
[0027] Furthermore, in step S5, the laminating layer material is squeezed into a laminating machine to laminarize the base paper, the screw temperature in the laminating machine is 225-270°C, and the temperature of the laminating zone is 220-240°C.
[0028] By adopting the above technical solution, setting the screw temperature within a reasonable range can ensure sufficient plasticization of the coating layer material, which helps to form a uniform and continuous coating layer; setting the temperature of the coating area within a reasonable range helps to form good adhesion between the coating material and the base paper, improve the overall strength and durability of the coating paper, and ensure its stability and reliability in subsequent use. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a bacterial colony diagram of the antibacterial activity of the film material used for paper cup material measured by the standard plate count method in Example 1;
[0030] Figure 2 This is a bacterial colony diagram of the antibacterial activity of the film material used for paper cup materials determined by the standard plate count method in Comparative Example 3. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with specific embodiments and drawings.
[0032] A degradable coated paper, comprising a base paper and a coating layer, wherein the coating layer comprises the following components by weight: 50-80 parts of polylactic acid, 10-25 parts of poly(hexane succinate terephthalate); 1-5 parts of biodegradable chitosan, 10-20 parts of modified talc, 0.3-1.0 parts of plasticizer, 0.2-1.0 parts of lubricant, 0.2-0.5 parts of antioxidant, and 0.2-0.5 parts of compatibilizer. The functions of each component are as follows:
[0033] Polylactic acid: As the main biodegradable polymer, it provides structural strength and toughness to the coating layer; and its own biodegradability helps reduce environmental pollution;
[0034] Poly(hexane succinate terephthalate) (PBAT): By blending with polylactic acid, the brittleness of polylactic acid is improved, and as a sticky substance, it provides stickiness in film and paper, thereby improving the performance of the entire coated paper;
[0035] Biodegradable chitosan: Chitosan has antibacterial properties, thus improving the antibacterial properties of the coating layer;
[0036] Modified talcum powder: significantly improves the overall mechanical properties of coated paper and plays a role in thermal insulation. As a natural mineral, it is low in cost.
[0037] Compatibilizer: enhances the compatibility between polylactic acid, poly(hexanediol succinate terephthalate) and biodegradable chitosan, and further increases the mechanical strength of the coated paper while maintaining the original good degradability and mechanical properties of polylactic acid;
[0038] Plasticizer: Increase the flexibility and ductility of the coating layer, enhance the plasticizing effect of the main material, and further improve compatibility; Lubricant: Reduce the friction and resistance of the coating layer during processing to ensure quality; Antioxidant: Inhibit the oxidation reaction of the coating layer during production, use and storage to ensure its stable performance.
[0039] The present application enhances the compatibility between polylactic acid, poly(hexylene succinate terephthalate) and modified talcum powder through the action of a compatibilizer, further increases the mechanical strength of the coated paper while maintaining the original good degradability and mechanical properties of polylactic acid, and the biodegradable chitosan has good antibacterial properties, which can achieve the antibacterial purpose after being combined with polylactic acid; at the same time, it helps to improve the processing performance of the material, making the coated paper easier to operate and form in the subsequent production process; and the brittleness of polylactic acid is improved by poly(hexylene succinate terephthalate), thereby improving the flexibility and ductility of the entire raw material, and as a viscous substance, provides viscosity to the film and paper; the addition of talcum powder can significantly improve the overall mechanical properties, thermal insulation properties, etc. of the coated paper, and as a natural mineral, it has low cost; the core raw materials of the entire degradable coated paper are all degradable materials or renewable materials, which help to reduce environmental pollution and promote sustainable development; the prepared coated material can withstand a gram weight of 0.6N / 30mm, which meets the requirements of general coated paper cups.
[0040] In a specific embodiment, the modified talc is food-grade talc, the size of the talc is 2500-3000 mesh, and the residual total water content is 0.02-0.1 wt%.
[0041] Food-grade talcum powder meets food safety standards, so adding it to biodegradable coated paper will not cause harm to human health, thus ensuring the safety of coated paper. In addition, if the size of talcum powder is kept within this numerical range, it can not only maintain the advantages of the plastic itself, but also form a reinforced support form with good mechanical properties, further enhance the physical properties of plastic products, and also have obvious thermal insulation effects; avoid too large a size, which is more likely to cause agglomeration, but is not conducive to melting and plasticizing with the resin.
[0042] In a specific embodiment, the plasticizer is acetyl tributyl citrate ATBC, the antioxidant is at least one of 1010 or 168, and the compatibilizer is Xibond2025.
[0043] In a specific embodiment, a method for preparing the degradable coated paper as described in any one of the above items comprises the following steps:
[0044] S1: drying polylactic acid, poly(hexane succinate terephthalate) and biodegradable chitosan;
[0045] S2: mixing a plasticizer, a compatibilizer, a lubricant, an antioxidant, and the dried polylactic acid, poly(hexane succinate terephthalate), and biodegradable chitosan to obtain a premix;
[0046] S3: adding modified talcum powder to the premix to obtain a mixed modified material;
[0047] S4: putting the mixed modified material into a twin-screw extruder for extrusion granulation to obtain a coating layer material;
[0048] S5: coating the base paper with a coating layer material to obtain a degradable coated paper.
[0049] By first drying polylactic acid, poly(hexanediol succinate terephthalate) and biodegradable chitosan, because they are materials with strong hygroscopicity, if not dried, they are easy to absorb moisture in the air during the mixing process, resulting in uneven mixing or affecting the performance of the coating layer material; then adding different raw materials in batches is conducive to controlling the reaction process, better controlling the production rhythm, avoiding uneven mixing or equipment overload caused by adding too many raw materials at one time, ensuring that each step achieves the expected effect, and helping to reduce the unevenness in the mixing process, thereby improving quality, improving production efficiency, and reducing waste and loss in the production process.
[0050] In a specific embodiment, the drying time of polylactic acid, poly(hexanediol succinate terephthalate) and biodegradable chitosan in step S1 is 7 to 9 hours, and the drying temperature is 45 to 55° C. Too high a temperature will cause the molecular chain to break and thermally degrade, thereby affecting the performance and quality of the coating layer material; too low a temperature will lead to slow drying progress, incomplete drying, and increased production costs and energy consumption; too long a drying time will increase production costs and energy consumption; if the drying time is too short, it may not be possible to completely remove the moisture in the raw materials.
[0051] In a specific embodiment, when the mixed modified material is fed into a twin-screw extruder for extrusion granulation in step S4, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone, and the temperature of the heating zone is set to rise from 120°C to 200°C; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is 170°C to 180°C.
[0052] In this embodiment, by controlling the temperature of the mixing zone in stages, it is not only helpful for the gradual melting and mixing of the mixed and modified materials, but also can optimize the energy consumption and efficiency in the extrusion granulation process.
[0053] In a specific embodiment, when the base paper is coated in step S5, the base paper thickness is 1 mm, and the coating amount of the coating material is 30 g / m 2 Precise control of the coating amount can achieve uniform distribution on the base paper; too little coating amount may cause leakage of the coated paper, poor adhesion, etc.; too much coating amount will cause waste of resources and increase costs.
[0054] In a specific embodiment, in step S5, the laminating layer material is squeezed into the laminating machine to laminat the base paper, and the screw temperature in the laminating machine is 225-270° C., and the laminating zone temperature is 220-240° C. Setting the screw temperature within a reasonable range can ensure that the laminating layer material is fully plasticized, which helps to form a uniform and continuous laminating layer; setting the laminating zone temperature within a reasonable range helps to form a good bond between the laminating material and the base paper, improve the overall strength and durability of the laminating paper, and ensure its stability and reliability in subsequent use.
[0055] In order to further facilitate the understanding of the solution of this application, the following examples are given:
[0056] Example 1
[0057] A degradable coated paper comprises a base paper and a coating layer, wherein the coating layer comprises the following components by weight: 72 parts of polylactic acid, 15 parts of poly(hexanediol succinate terephthalate); 3 parts of biodegradable chitosan, 10 parts of modified talcum powder (the mesh number of the talcum powder is 2500 meshes), 0.3 parts of a plasticizer, 0.2 parts of a lubricant, 0.2 parts of an antioxidant, and 0.3 parts of a compatibilizer; the 0.2 parts of the antioxidant are a mixture of 0.1 parts of an antioxidant 1010 and 0.1 parts of an antioxidant 168; the compatibilizer may be Xibond 2025 from Polyscop; the antioxidants, compatibilizers and talcum powder in the following embodiments and comparative examples are the same as those in this embodiment;
[0058] A method for preparing degradable coated paper comprises the following steps:
[0059] S1: According to the above weight parts, polylactic acid, poly(hexane succinate terephthalate) and biodegradable chitosan are placed in a forced air drying oven, dried at 50° C. for 4 hours to remove moisture, taken out, and placed in a desiccator for standby use;
[0060] S2: adding plasticizer, compatibilizer, lubricant, antioxidant and dried polylactic acid, poly(hexane terephthalate succinate) and biodegradable chitosan into a high-speed mixer and stirring at a speed of 800 rpm for 5 min to obtain a premix;
[0061] S3: Add modified talcum powder to a high-speed mixer, and stir at high speed at a speed of 600 rpm for 5 min to add modified talcum powder to the premix to obtain a mixed modified material;
[0062] S4: vacuum feeding the mixed modified material into a twin-screw extruder for extrusion granulation to obtain a coating layer material; specifically, the process steps of the twin-screw extruder are: 150 rpm screw main engine speed, 60 rpm feeding speed, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone, the heating zone is sequentially set to 120°C, 170°C and 200°C; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is sequentially set to 180°C and 170°C, melt blending, extrusion granulation, and then cooling by a fan cold belt, cutting and granulation by a granulator to obtain a composite coating layer material;
[0063] S5: coating the coating layer material on the base paper to obtain degradable coated paper; specifically, placing the coating layer material in a blast drying oven, setting the temperature to 60°C, and taking it out after drying for 1 hour; squeezing the dried coating layer material into a coating machine to coat the base paper, and the screw temperature in the coating machine (here refers to the temperature interval from the feed port to the screw outlet) is set to 225°C, 240°C, 250°C, 260°C, and 270°C in sequence; the temperature of the coating area is set to 220°C, 230°C, 230°C, 240°C, 230°C, 225°C, and 220°C in sequence.
[0064] Example 2
[0065] A degradable coated paper comprises a base paper and a coating layer, wherein the coating layer comprises the following components by weight: 67 parts of polylactic acid, 15 parts of poly(hexanediol succinate terephthalate); 3 parts of biodegradable chitosan, 15 parts of modified talcum powder (the mesh number of the talcum powder is 2500 meshes), 0.3 parts of a plasticizer, 0.2 parts of a lubricant, 0.2 parts of an antioxidant, and 0.3 parts of a compatibilizer; the 0.2 parts of the antioxidant is a mixture of 0.1 parts of antioxidant 1010 and 0.1 parts of antioxidant 168;
[0066] A method for preparing degradable coated paper comprises the following steps:
[0067] S1: According to the above weight parts, polylactic acid, poly(hexane succinate terephthalate) and biodegradable chitosan are placed in a forced air drying oven, dried at 50° C. for 4 hours to remove moisture, taken out, and placed in a desiccator for standby use;
[0068] S2: adding plasticizer, compatibilizer, lubricant, antioxidant and dried polylactic acid, poly(hexane terephthalate succinate) and biodegradable chitosan into a high-speed mixer and stirring at a speed of 800 rpm for 5 min to obtain a premix;
[0069] S3: Add modified talcum powder to a high-speed mixer, and stir at high speed at a speed of 600 rpm for 5 min to add modified talcum powder to the premix to obtain a mixed modified material;
[0070] S4: vacuum feeding the mixed modified material into a twin-screw extruder for extrusion granulation to obtain a coating layer material; specifically, the process steps of the twin-screw extruder are: 150 rpm screw main engine speed, 60 rpm feeding speed, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone, the heating zone is sequentially set to 120°C, 170°C and 200°C; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is sequentially set to 180°C and 170°C, melt blending, extrusion granulation, and then cooling by a fan cold belt, cutting and granulation by a granulator to obtain a composite coating layer material;
[0071] S5: coating the coating layer material on the base paper to obtain degradable coated paper; specifically, placing the coating layer material in a blast drying oven, setting the temperature to 60°C, and taking it out after drying for 1 hour; squeezing the dried coating layer material into a coating machine to coat the base paper, and the screw temperature in the coating machine (here refers to the temperature interval from the feed port to the screw outlet) is set to 225°C, 240°C, 250°C, 260°C, and 270°C in sequence; the temperature of the coating area is set to 220°C, 230°C, 230°C, 240°C, 230°C, 225°C, and 220°C in sequence.
[0072] Example 3
[0073] A degradable coated paper comprises a base paper and a coating layer, wherein the coating layer comprises the following components by weight: 62 parts of polylactic acid, 15 parts of poly(hexanediol succinate terephthalate); 3 parts of biodegradable chitosan, 20 parts of modified talcum powder (the mesh number of the talcum powder is 2500 meshes), 0.3 parts of a plasticizer, 0.2 parts of a lubricant, 0.2 parts of an antioxidant, and 0.3 parts of a compatibilizer; the 0.2 parts of the antioxidant is a mixture of 0.1 parts of antioxidant 1010 and 0.1 parts of antioxidant 168;
[0074] A method for preparing degradable coated paper comprises the following steps:
[0075] S1: According to the above weight parts, polylactic acid, poly(hexane succinate terephthalate) and biodegradable chitosan are placed in a forced air drying oven, dried at 50° C. for 4 hours to remove moisture, taken out, and placed in a desiccator for standby use;
[0076] S2: adding plasticizer, compatibilizer, lubricant, antioxidant and dried polylactic acid, poly(hexane terephthalate succinate) and biodegradable chitosan into a high-speed mixer and stirring at a speed of 800 rpm for 5 min to obtain a premix;
[0077] S3: Add modified talcum powder to a high-speed mixer, and stir at high speed at a speed of 600 rpm for 5 min to add modified talcum powder to the premix to obtain a mixed modified material;
[0078] S4: vacuum feeding the mixed modified material into a twin-screw extruder for extrusion granulation to obtain a coating layer material; specifically, the process steps of the twin-screw extruder are: 150 rpm screw main engine speed, 60 rpm feeding speed, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone, the heating zone is sequentially set to 120°C, 170°C and 200°C; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is sequentially set to 180°C and 170°C, melt blending, extrusion granulation, and then cooling by a fan cold belt, cutting and granulation by a granulator to obtain a composite coating layer material;
[0079] S5: coating the coating layer material on the base paper to obtain degradable coated paper; specifically, placing the coating layer material in a blast drying oven, setting the temperature to 60°C, and taking it out after drying for 1 hour; squeezing the dried coating layer material into a coating machine to coat the base paper, and the screw temperature in the coating machine (here refers to the temperature interval from the feed port to the screw outlet) is set to 225°C, 240°C, 250°C, 260°C, and 270°C in sequence; the temperature of the coating area is set to 220°C, 230°C, 230°C, 240°C, 230°C, 225°C, and 220°C in sequence.
[0080] Comparative Example 1
[0081] A degradable coated paper, comprising a base paper and a coated layer, wherein the coating layer comprises the following components by weight: 72 parts of polylactic acid, 28 parts of poly(hexamethylene succinate terephthalate), 0.3 parts of a plasticizer, 0.2 parts of a lubricant, 0.2 parts of an antioxidant, and 0.3 parts of a compatibilizer; the 0.2 parts of the antioxidant is a mixture of 0.1 parts of an antioxidant 1010 and 0.1 parts of an antioxidant 168;
[0082] A method for preparing degradable coated paper comprises the following steps:
[0083] S1: According to the above weight parts, polylactic acid and poly(hexylene succinate terephthalate) are placed in a forced air drying oven, dried at 50° C. for 4 hours to remove moisture, taken out, and placed in a desiccator for standby use;
[0084] S2: adding plasticizer, compatibilizer, lubricant, antioxidant and dried polylactic acid and poly(hexane terephthalate succinate) into a high-speed mixer and stirring at a speed of 800 rpm for 5 min to obtain a premix;
[0085] S3: vacuum feeding the premixed material into a twin-screw extruder for extrusion granulation to obtain a coating layer material; specifically, the process steps of the twin-screw extruder are: 150 rpm screw main engine speed, 60 rpm feeding speed, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone, the heating zone is set to 120°C, 170°C and 200°C in sequence; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is set to 180°C and 170°C in sequence, melt blending, extrusion granulation, and then cooling by a fan cold belt, cutting and granulation by a granulator to obtain a composite coating layer material;
[0086] S4: coating the base paper with coating layer material to obtain degradable coated paper; specifically, placing the coating layer material in a blast drying oven, setting the temperature to 60°C, and taking it out after drying for 1 hour; squeezing the dried coating layer material into a coating machine to coat the base paper, and the screw temperature in the coating machine (here refers to the temperature interval from the feed port to the screw outlet) is set to 225°C, 240°C, 250°C, 260°C, and 270°C in sequence; the temperature of the coating area is set to 220°C, 230°C, 230°C, 240°C, 230°C, 225°C, and 220°C in sequence.
[0087] Comparative Example 2
[0088] A degradable coated paper, comprising a base paper and a coated layer, wherein the coating layer comprises the following components by weight: 72 parts of polylactic acid, 25 parts of poly(hexanediol succinate terephthalate), 3 parts of biodegradable chitosan, 0.3 parts of a plasticizer, 0.2 parts of a lubricant, 0.2 parts of an antioxidant, and 0.3 parts of a compatibilizer; the 0.2 parts of the antioxidant is a mixture of 0.1 parts of an antioxidant 1010 and 0.1 parts of an antioxidant 168;
[0089] A method for preparing degradable coated paper comprises the following steps:
[0090] S1: According to the above weight parts, polylactic acid, poly(hexane succinate terephthalate) and biodegradable chitosan are placed in a forced air drying oven, dried at 50° C. for 4 hours to remove moisture, taken out, and placed in a desiccator for standby use;
[0091] S2: adding plasticizer, compatibilizer, lubricant, antioxidant and dried polylactic acid, poly(hexane terephthalate succinate) and biodegradable chitosan into a high-speed mixer and stirring at a speed of 800 rpm for 5 min to obtain a premix;
[0092] S3: vacuum feeding the premixed material into a twin-screw extruder for extrusion granulation to obtain a coating layer material; specifically, the process steps of the twin-screw extruder are: 150 rpm screw main engine speed, 60 rpm feeding speed, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone, the heating zone is set to 120°C, 170°C and 200°C in sequence; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is set to 180°C and 170°C in sequence, melt blending, extrusion granulation, and then cooling by a fan cold belt, cutting and granulation by a granulator to obtain a composite coating layer material;
[0093] S4: coating the base paper with coating layer material to obtain degradable coated paper; specifically, placing the coating layer material in a blast drying oven, setting the temperature to 60°C, and taking it out after drying for 1 hour; squeezing the dried coating layer material into a coating machine to coat the base paper, and the screw temperature in the coating machine (here refers to the temperature interval from the feed port to the screw outlet) is set to 225°C, 240°C, 250°C, 260°C, and 270°C in sequence; the temperature of the coating area is set to 220°C, 230°C, 230°C, 240°C, 230°C, 225°C, and 220°C in sequence.
[0094] Comparative Example 3
[0095] A degradable coated paper comprises a base paper and a coating layer, wherein the coating layer comprises the following components by weight: 72 parts of polylactic acid, 18 parts of poly(hexamethylene succinate terephthalate), 10 parts of modified talcum powder (the mesh number of the talcum powder is 2500 meshes), 0.3 parts of a plasticizer, 0.2 parts of a lubricant, 0.2 parts of an antioxidant, and 0.3 parts of a compatibilizer; the 0.2 parts of the antioxidant is a mixture of 0.1 parts of antioxidant 1010 and 0.1 parts of antioxidant 168;
[0096] A method for preparing degradable coated paper comprises the following steps:
[0097] S1: According to the above weight parts, polylactic acid and poly(hexylene succinate terephthalate) are placed in a forced air drying oven, dried at 50° C. for 4 hours to remove moisture, taken out, and placed in a desiccator for standby use;
[0098] S2: adding a plasticizer, a compatibilizer, a lubricant, an antioxidant, and the dried polylactic acid and poly(hexane terephthalate succinate) into a high-speed mixer and stirring at a high speed of 800 rpm for 5 min to obtain a premix;
[0099] S3: Add modified talcum powder to a high-speed mixer, and stir at high speed at a speed of 600 rpm for 5 min to add modified talcum powder to the premix to obtain a mixed modified material;
[0100] S4: vacuum feeding the mixed modified material into a twin-screw extruder for extrusion granulation to obtain a coating layer material; specifically, the process steps of the twin-screw extruder are: 150 rpm screw main engine speed, 60 rpm feeding speed, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone, the heating zone is sequentially set to 120°C, 170°C and 200°C; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is sequentially set to 180°C and 170°C, melt blending, extrusion granulation, and then cooling by a fan cold belt, cutting and granulation by a granulator to obtain a composite coating layer material;
[0101] S5: coating the coating layer material on the base paper to obtain degradable coated paper; specifically, placing the coating layer material in a blast drying oven, setting the temperature to 60°C, and taking it out after drying for 1 hour; squeezing the dried coating layer material into a coating machine to coat the base paper, and the screw temperature in the coating machine (here refers to the temperature interval from the feed port to the screw outlet) is set to 225°C, 240°C, 250°C, 260°C, and 270°C in sequence; the temperature of the coating area is set to 220°C, 230°C, 230°C, 240°C, 230°C, 225°C, and 220°C in sequence.
[0102] Comparative Example 4
[0103] A degradable coated paper comprises a base paper and a coating layer, wherein the coating layer comprises the following components by weight: 72 parts of polylactic acid, 15 parts of poly(hexanediol succinate terephthalate), 3 parts of biodegradable chitosan; 10 parts of calcium carbonate (the mesh size of the calcium carbonate is 2500 mesh); 0.3 parts of a plasticizer, 0.2 parts of a lubricant, 0.2 parts of an antioxidant, and 0.3 parts of a compatibilizer; the 0.2 parts of the antioxidant is a mixture of 0.1 parts of an antioxidant 1010 and 0.1 parts of an antioxidant 168;
[0104] A method for preparing degradable coated paper comprises the following steps:
[0105] S1: According to the above weight parts, polylactic acid, poly(hexane succinate terephthalate) and biodegradable chitosan are placed in a forced air drying oven, dried at 50° C. for 4 hours to remove moisture, taken out, and placed in a desiccator for standby use;
[0106] S2: adding plasticizer, compatibilizer, lubricant, antioxidant and dried polylactic acid, poly(hexane terephthalate succinate) and biodegradable chitosan into a high-speed mixer and stirring at a speed of 800 rpm for 5 min to obtain a premix;
[0107] S3: Add calcium carbonate to a high-speed mixer and stir at high speed at a speed of 600 rpm for 5 min to add calcium carbonate to the premix to obtain a mixed modified material;
[0108] S4: vacuum feeding the mixed modified material into a twin-screw extruder for extrusion granulation to obtain a coating layer material; specifically, the process steps of the twin-screw extruder are: 150 rpm screw main engine speed, 60 rpm feeding speed, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone, the heating zone is sequentially set to 120°C, 170°C and 200°C; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is sequentially set to 180°C and 170°C, melt blending, extrusion granulation, and then cooling by a fan cold belt, cutting and granulation by a granulator to obtain a composite coating layer material;
[0109] S5: coating the coating layer material on the base paper to obtain degradable coated paper; specifically, placing the coating layer material in a blast drying oven, setting the temperature to 60°C, and taking it out after drying for 1 hour; squeezing the dried coating layer material into a coating machine to coat the base paper, and the screw temperature in the coating machine (here refers to the temperature interval from the feed port to the screw outlet) is set to 225°C, 240°C, 250°C, 260°C, and 270°C in sequence; the temperature of the coating area is set to 220°C, 230°C, 230°C, 240°C, 230°C, 225°C, and 220°C in sequence.
[0110] In order to test the antibacterial activity of the prepared paper cup material against bacteria, Example 1 and Comparative Example 3 were respectively subjected to the following experiments: The antibacterial activity of the film material for paper cup material was determined by the standard plate count method. The samples prepared by the examples and comparative examples were cut into 1×1 cm film sheets, soaked in 75% ethanol solution for disinfection for 30 minutes, and then rinsed with phosphate buffer (PBS, 10mM, pH 6.3) for 3 times. Take the methicillin-resistant Staphylococcus aureus (MRSA) in the logarithmic growth period, and the standard strain was purchased from ATCC. 1mL of methicillin-resistant Staphylococcus aureus (MRSA) bacterial solution (pH 6.3, OD600 0.4-0.5) was shaken for 30 minutes with the experimental example and the comparative example. Then, centrifuged at 3000rpm for 5 minutes, and the precipitate was washed 3 times with PBS. The obtained bacterial suspension was appropriately diluted, then evenly spread on the LB agar plate, and cultured at 37°C for another 24 hours.
[0111] Use an automated colony counter to obtain images and counts of bacterial colonies. The results are shown in Figure 1 and Figure 2 As shown, by comparing the example with the comparative example, it can be clearly seen that the number of bacterial colonies is significantly reduced, thereby obtaining that the biofilm prepared by the example of the present application has an excellent antibacterial effect.
[0112] In order to detect the mechanical properties and thermal insulation properties of Examples 1-3 and Comparative Examples 1-4, mechanical properties tests and thermal insulation properties tests were performed. The thermal insulation properties test was performed by pouring 90°C water into a cup in a constant temperature environment of 25°C and recording the temperature every 6 hours. The specific data are shown in Table 1:
[0113] Table 1 Performance data of biodegradable thermal insulation coated paper
[0114]
[0115] As can be seen from Table 1, the degradable coated paper prepared by the present application can take into account the multiple functions of degradation, heat preservation and antibacterial, and its mechanical properties are not affected; and the thermal insulation performance of the entire coated paper is effectively guaranteed by the addition of modified talcum powder, because the modified talcum powder has a flaky structure, which enables the modified talcum powder to form a layered distribution in the coated paper, and at the same time has a lower thermal conductivity. Therefore, compared with calcium carbonate, when it is blended with polylactic acid and biodegradable chitosan, the thermal insulation effect is greater than the thermal insulation effect of calcium carbonate, polylactic acid and biodegradable chitosan blended.
[0116] The examples described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.
Claims
1. A degradable coated paper, comprising a base paper and a coated layer, characterized in that: The materials of the coating layer include the following components in parts by weight: 50 to 80 parts of polylactic acid, 10 to 25 parts of poly(hexane succinate terephthalate); 1 to 5 parts of biodegradable chitosan, 10 to 20 parts of modified talcum powder, 0.3 to 1.0 parts of plasticizer, 0.2 to 1.0 parts of lubricant, 0.2 to 0.5 parts of antioxidant, and 0.2 to 0.5 parts of compatibilizer; the modified talcum powder is talcum powder with a silane coupling agent coated on its surface.
2. The biodegradable coated paper according to claim 1, characterized in that: The modified talcum powder is food-grade talcum powder, the size of the modified talcum powder is 2500-3000 mesh, and the residual total water content is 0.02-0.1wt%.
3. The biodegradable coated paper according to claim 1, characterized in that: The plasticizer is acetyl tributyl citrate ATBC, and the antioxidant is at least one of 1010 or 168.
4. A method for preparing the degradable coated paper according to any one of claims 1 to 3, characterized in that: The steps include: S1: drying polylactic acid, poly(hexane succinate terephthalate) and biodegradable chitosan; S2: mixing a plasticizer, a compatibilizer, a lubricant, an antioxidant, and the dried polylactic acid, poly(hexane succinate terephthalate), and biodegradable chitosan to obtain a premix; S3: adding modified talcum powder to the premix to obtain a mixed modified material; S4: putting the mixed modified material into a twin-screw extruder for extrusion granulation to obtain a coating layer material; S5: coating the base paper with a coating layer material to obtain a degradable coated paper.
5. The method for preparing a degradable coated paper according to claim 4, characterized in that: In the step S1, the drying time of polylactic acid, poly(hexanediol succinate terephthalate) and biodegradable chitosan is 7 to 9 hours, and the drying temperature is 45 to 55°C.
6. The method for preparing a degradable coated paper according to claim 4, characterized in that: When the mixed modified material is fed into the twin-screw extruder for extrusion granulation in step S4, the mixing zone includes a heating zone, a heat preservation zone and a cooling zone. The temperature of the heating zone is set to rise from 120°C to 200°C; the temperature of the heat preservation zone is 200°C, and the temperature of the cooling zone is 170°C to 180°C.
7. The method for preparing a degradable coated paper according to claim 4, characterized in that: When the base paper is coated in step S5, the base paper thickness is 1 mm, and the coating amount of the coating material is 30 g / m 2 .
8. The method for preparing a degradable coated paper according to claim 4 or 7, characterized in that: In the step S5, the laminating layer material is squeezed into the laminating machine to laminat the base paper, the screw temperature in the laminating machine is 225-270°C, and the laminating zone temperature is 220-240°C.
Citation Information
Patent Citations
Biodegradable low-temperature-resistant coated paper and preparation method thereof
CN112796167A
Biodegradable PLA laminating material and laminating product based on same
CN117845650A
Cited By
Domestic compost modified polylactic acid suitable for film spraying and preparation method of domestic compost modified polylactic acid
CN119711241A
A kind of biodegradable fully bio-based coated paper capable of home composting and preparation method thereof
CN119736811A
Antibacterial coated paper and preparation method thereof
CN121250711A
Antibacterial coated paper and method for making the same
CN121250711B